Family quality of life and family-school collaboration during the COVID-19 pandemic: perceptions of Swedish parents of adolescents with special educational needs - Zakirova-Engstrand, Rano; Wilder, Jenny (Frontiers in Education, 2024)
Compared to other countries, Sweden did not introduce sudden lockdowns and school closures during the COVID-19 pandemic. Instead, the country chose a less restrictive approach to managing the pandemic, such as staying at home with any symptoms of cold or COVID-19, washing hands, and maintaining social distancing. Preschools and compulsory schools remained open. In this context, limited evidence exists about how Swedish families of students with special educational needs and disabilities (SEND) experienced collaboration with school professionals to support their children during the COVID-19, and how the pandemic affected parents' perceptions of quality of their family life. The present study investigated parental perceptions of satisfaction with family-school collaboration and with family quality of life during the COVID-19 pandemic. Twenty-six parents of students with SEND who attended general lower secondary schools (grades 7-9) completed a survey using three measures: the demographic questionnaire, the Beach Center Family Quality of Life scale (FQOL), and the Family-School Collaboration scale the adapted version of the original Beach Center Family-Professional Partnership Scale. Descriptive statistics, Pearson correlations were used to analyze data. Parents felt less satisfied with family-school collaboration related to child-oriented aspects; they were least satisfied with their emotional well-being aspect of family quality of life. Strong, significant and positive associations were found between family-school collaboration and disability-related support aspect of FQOL. The findings point to the importance of family-school partnerships in promoting students' positive school achievements, and in enhancing FQOL. The findings have practical implications for professional development of pre-and in-service teachers within the existing curricula of teacher preparation programs. Implications for further research are discussed given the study's small sample size and challenges in recruitment of participants.